2004
DOI: 10.1074/jbc.m400261200
|View full text |Cite
|
Sign up to set email alerts
|

SRP-2 Is a Cross-class Inhibitor That Participates in Postembryonic Development of the Nematode Caenorhabditis elegans

Abstract: High molecular weight serpins are members of a large superfamily of structurally conserved proteins that inactivate target proteinases by a suicide substrate-like mechanism. In vertebrates, different clades of serpins distribute predominantly to either the intracellular or extracellular space. Although much is known about the function, structure, and inhibitory mechanism of circulating serpins such as ␣ 1 -antitrypsin (SERPINA1) and antithrombin III (SERPINC1), relatively little is known about the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 36 publications
(34 reference statements)
1
50
2
2
Order By: Relevance
“…The nematode Caenhorabditis elegans has also been shown to encode a potent gzmB inhibitor, Srp-2. 102 The P1 residue is a Glu, suggesting that caspases are not the intended target proteases, and the kinetics seem to suggest a physiologically relevant interaction with gzmB (SI ¼ 1.75, k ass ¼ 2.3 Â 10 4 M À1 s À1 ). 102 However, it must be asked why C. elegans, which neither produces endogenous gzmB nor infects an organism that produces gzmB, and feeds on bacteria that do not produce gzmB, would evolve a potent inhibitor of this protease.…”
Section: Are Rodents Useful For Studying Serpin-granzyme Interactions?mentioning
confidence: 99%
See 1 more Smart Citation
“…The nematode Caenhorabditis elegans has also been shown to encode a potent gzmB inhibitor, Srp-2. 102 The P1 residue is a Glu, suggesting that caspases are not the intended target proteases, and the kinetics seem to suggest a physiologically relevant interaction with gzmB (SI ¼ 1.75, k ass ¼ 2.3 Â 10 4 M À1 s À1 ). 102 However, it must be asked why C. elegans, which neither produces endogenous gzmB nor infects an organism that produces gzmB, and feeds on bacteria that do not produce gzmB, would evolve a potent inhibitor of this protease.…”
Section: Are Rodents Useful For Studying Serpin-granzyme Interactions?mentioning
confidence: 99%
“…102 The P1 residue is a Glu, suggesting that caspases are not the intended target proteases, and the kinetics seem to suggest a physiologically relevant interaction with gzmB (SI ¼ 1.75, k ass ¼ 2.3 Â 10 4 M À1 s À1 ). 102 However, it must be asked why C. elegans, which neither produces endogenous gzmB nor infects an organism that produces gzmB, and feeds on bacteria that do not produce gzmB, would evolve a potent inhibitor of this protease. The inhibition is more likely coincidental, with Srp-2 actually inhibiting a bacterial subtilisin-like acidic protease, as subtilisin is efficiently inhibited by SERPINB9.…”
Section: Are Rodents Useful For Studying Serpin-granzyme Interactions?mentioning
confidence: 99%
“…In addition, SRP-3 was expressed predominately in both larval and adult muscles cells. In a previous study we showed that SRP-2 was a dual cross-class inhibitor of granzyme B serine peptidases and papain-like cysteine peptidases and that this inhibitor was expressed in intestinal and hypodermal cells (5). Thus, these two serpins IC complement one another by extending the family's overall inhibitory profile and tissue expression pattern in C. elegans.…”
Section: Discussionmentioning
confidence: 91%
“…While in silico analysis is helpful in predicting the overall repertoire of serpins IC in different species, these assessments are imperfect and require confirmation by experimentation. To date, only srp-2 has been shown to encode for a bona fide inhibitory type serpin IC in C. elegans (5). SRP-2 is a dual cross-class inhibitor and neutralizes granzyme Blike serine peptidases and cathepsin-L-like lysosomal cysteine peptidases and is expressed highly in the hypodermal and intestinal cells of larval and adult worms.…”
mentioning
confidence: 99%
“…Следовательно, контроль серпинами за маршрутами эндоцитоза и экзоцитоза является древним способом защиты основных внутриклеточных путей экспорта и импорта от неконтролируемой эндогенной или чужеродной протеолитической активности (Van Gent D. et al, 2003;Pak et al, 2004;Kumar and Ragg, 2008). Серпины найдены у разных видов царства растений и в зеленых водорослях.…”
unclassified